Unsteady Convective Heat and Mass Transfer Flow in a Thin Liquid Film Over Moving Sheet in a Saturated Permeable Surface - Hasanuzzaman, Md; Afroj, Romana; Hossain, MM Touhid (Journal of Engineering Science, 2021)
a